2010
DOI: 10.1124/jpet.109.163444
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and Antitumor Activity of ABC294640, a Selective Inhibitor of Sphingosine Kinase-2

Abstract: Sphingolipid-metabolizing enzymes control the dynamic balance of the cellular levels of important bioactive lipids, including the apoptotic compound ceramide and the proliferative compound sphingosine 1-phosphate (S1P). Many growth factors and inflammatory cytokines promote the cleavage of sphingomyelin and ceramide leading to rapid elevation of S1P levels through the action of sphingosine kinases (SK1 and SK2). SK1 and SK2 are overexpressed in a variety of human cancers, making these enzymes potential molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
386
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 290 publications
(400 citation statements)
references
References 38 publications
13
386
1
Order By: Relevance
“…A current lead SK2 inhibitor, ABC294640, was developed to improve the oral bioavailability and enzyme specificity that hampered the development of other lipidmimetic SK inhibitors (French et al, 2010). We have shown previously that ABC294640 has anti-inflammatory activity in vivo (Maines et al, 2006(Maines et al, , 2008Smith et al, 2008) and in this work that it also has antitumor activity (Fig.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…A current lead SK2 inhibitor, ABC294640, was developed to improve the oral bioavailability and enzyme specificity that hampered the development of other lipidmimetic SK inhibitors (French et al, 2010). We have shown previously that ABC294640 has anti-inflammatory activity in vivo (Maines et al, 2006(Maines et al, , 2008Smith et al, 2008) and in this work that it also has antitumor activity (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…6). Pharmacokinetic studies of ABC294640 indicate that the compound reaches a peak plasma concentration of approximately 20 M after an oral dose of 50 mg/kg and is eliminated with a half-time of clearance of approximately 4.5 h (French et al, 2010), suggesting that even more pronounced antitumor effects can be obtained with higher doses and/or more frequent administration. ABC294640 is currently in certified Good Laboratory Practice toxicology studies and is expected to enter clinical trials in 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, exogenous expression of MYC resulted in a degree of resistance to SK2 inhibition by ABC294640. SK2 inhibition has been associated with both caspasedependent (45) and -independent cell death (46), with autophagy being involved in the latter. Autophagy also has cell survival roles (47) and although SK2 inhibition induced autophagy in ALL cells, this was not the cause of cell death, a situation similar to that following FTY720 exposure (48).…”
Section: Discussionmentioning
confidence: 99%
“…However, some have suggested that overexpressing Sphk isoforms may change their subcellular localization and alter endogenous function. 21,22 Despite increased understanding of the importance of sphingolipid signaling in anticancer drug resistance, pharmacologically targeting this pathway as a therapeutic has been inhibited by a lack of small molecule inhibitors. In this study we use the recently discovered selective sphingosine kinase-2 inhibitor, ABC294640, to elucidate the role of Sphk2 in breast cancer biology.…”
Section: Introductionmentioning
confidence: 99%